Portretul unui neam: Captivus Septemcastrensis, princeps cantemirius - Ioana Costa (Revista de Istorie și Teorie Literară)
The Romanian literature written in Latin offers two extended portraits of the Ottoman world: besides the famous Historia Othmanica of Dimitrie Cantemir, there is Tractatus de moribus, condicionibus et nequicia Turcorumi, composed by a writer from Sebes, known under several names (Georg Captivus Septemcastrensis, Georgius de Hungaria, The Romosan Student). The explicit Christian perspective and, nevertheless, the direct knowledge of the Ottoman realia are elements that connect the two writings, separated by a century and a half of impetuous history. Related to different moments of the Ottoman Empire, the two works, belonging to authors placed in totally opposed positions (slave and prince), ought to have a parallel lecture.